2010
DOI: 10.1089/thy.2009.0125
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage of Thyroid Volume in Sunitinib-Treated Patients with Renal-Cell Carcinoma: A Potential Marker of Irreversible Thyroid Dysfunction?

Abstract: Morphological changes of the thyroid gland can be associated with the well-described adverse biochemical effects of treatment with sunitinib and can be a potential marker of the irreversible organ damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…As described above, Rogiers et al (2010) reported two cancer patients with a pre-existing nodular thyroid gland who developed hypothyroidism and showed marked shrinkage of the thyroid during treatment with sunitinib, necessitating permanent thyroid hormone replacement therapy even after discontinuation of sunitinib. They suggested the possibility that shrinkage of thyroid volume in sunitinib-treated patients could be a potential marker of irreversible organ damage.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As described above, Rogiers et al (2010) reported two cancer patients with a pre-existing nodular thyroid gland who developed hypothyroidism and showed marked shrinkage of the thyroid during treatment with sunitinib, necessitating permanent thyroid hormone replacement therapy even after discontinuation of sunitinib. They suggested the possibility that shrinkage of thyroid volume in sunitinib-treated patients could be a potential marker of irreversible organ damage.…”
Section: Discussionmentioning
confidence: 81%
“…In a recent report, sunitinib-induced shrinkage of the thyroid gland appears to have been a potential marker of irreversible organ damage, resulting in persistent hypothyroidism (Rogiers et al 2010). …”
mentioning
confidence: 99%
“…However, the mechanisms involved in sunitinib-induced hypothyroidism are still unclear. The reduction in capillary blood flow caused by VEGFR inhibition may explain the marked decrease in thyroid size [13][14][15]. Another mechanism involved in thyroid dysfunction may be the inhibition of thyroid peroxidase leading to reduced synthesis of thyroid hormone [4].…”
Section: ※3mentioning
confidence: 99%
“…Supporting evidence for this theory include findings that thyroid cells express VEGF and VEGFR mRNA, and preclinical studies in mouse models have shown glandular capillary regression with TKI exposure [115]. In humans, case reports demonstrated reduced thyroid volume and reduced vascularity by Doppler ultrasound [116,117], with rapid increase in the size of the thyroid with cessation of sunitinib. This reduced thyroid volume secondary to reduced blood flow, may also explain the impaired radioactive iodine uptake in vivo, but not in vitro [118].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 96%